Computational Design of a Novel Dithranol–Salicylic Acid Antipsoriatic Prodrug for Esterase-Activated Topical Drug Delivery - Natália Andrýsková; Jozef Motyčka; Melánia Babincová; Peter Babinec; Mária Šimaljaková (Applied Sciences, 2024)
Psoriasis is a chronic autoimmune skin disorder characterized by the rapid overproduction of skin cells, resulting in the formation of red, inflamed, and scaly patches or plaques on the skin. Dithranol, also known as anthralin, is a very effective topical medication used in the treatment of psoriasis, with several shortcomings like photo-instability; staining skin, clothing, and bedding; and causing skin irritation. Antiproliferative dithranol is frequently used in combination therapy with keratolytic salicylic acid. We have therefore proposed a novel topical antipsoriatic prodrug comprising dithranol and salicylic acid joined together with an ester bond, specifically 8-hydroxy-9-oxo-9,10-dihydroanthracen-1-yl-2-hydroxybenzoate. An ester bond is cleavable by endogenous esterase hydrolyzing this bond and releasing dithranol and salicylic acid in a 1:1 stoichiometric ratio. We performed an exhaustive theoretical analysis of this molecule using the reliable computational methods of quantum chemistry and ADME in silico studies to investigate its biological and pharmacokinetic activities. We found its molecular structure, vibrational spectra, molecular orbitals, MEP (molecular electric potential), UV-VIS spectra, and TDOS (total density of states), and we performed an RDG (reduced density gradient) analysis. The obtained results may be useful for the understanding of its properties, which may assist in the synthesis and further experimental study of this possible antipsoriatic dual-action prodrug with reduced adverse effects and enhanced therapeutic efficacy.